Mortality due to Diabetes Mellitus in northeastern Brazil from 2014 to 2018 - Negreiros, Erika Cristina Moura da Silva; Silva, Laiany Caroline dos Santos; Araújo, Ana Carolina Ribeiro de Araújo e; Dias, Laura Rosa Carvalho; Moura, Luís Victor Moraes de; Rosa, Isabella Mota Santa; Filho, José Mário de Menezes; Marques, Consuelo Penha Castro (Seven Editora, 2024)
Diabetes Mellitus (DM) is a group of metabolic disorders marked by hyperglycemia, and is classified into several subtypes. It is currently a major challenge for the world’s health systems, with a progressive increase in impact due to urbanization and industrialization, as a result of unhealthy lifestyle habits. This metabolic disorder is among the five main mortality risks in the world, and can trigger acute or chronic complications in the cardiovascular, renal and neurological system, usually with targeted changes in organs, specifically, heart, kidneys, brain and blood vessels in general. This study aims to analyze the mortality from Diabetes Mellitus in the Brazilian Northeast Region between the years 2014 to 2018, through an epidemiological study of time series, with secondary data DATASUS- Ministry of Health, with research of the variables: sex, race, education, age group, marital status, place of occurrence, Northeast, ICD-10 category, diabetes. The data will be expressed in absolute numbers, percentages and descriptive statistics. 101,636 cases were found, 56% of which were female and the highest number, respectively, in the states of Bahia and Pernambuco. Most deaths are concentrated in the category of non-conventional diabetes mellitus, followed by the non-insulin-dependent and insulin-dependent category. As for education, 35% of deaths are in the category of no schooling and 23% with 1 to 3 years of study. Regarding the age group, most deaths are observed from the age of 80, with an increase in the number as the age group increases. There is a prevalence of 58% of deaths in the brown race, followed by white and black race, respectively. Most deaths occurred in married people, with 39% of cases, followed by widowers, 29%, and singles 24%. The most registered place of occurrence was in the hospital, with 63% of deaths and 31% in another health establishment. The epidemiological profile outlined points to the need for articulation of regionalized and peculiar strategies, with health promotion and education, aiming at better management of DM and reduction of mortality rates, especially those of early age groups. DOI:https://doi.org/10.56238/sevened2023.006-137